Developing an Arrayed CRISPR-Cas9 Co-Culture Screen for Immuno-Oncology Target ID. (July 2020) - Gee, Sarah; Nelson, Nadine; Bornot, Aurelie; Carter, Nikki; Cuomo, Maria Emanuela; Dovedi, Simon J.; Smith, Paul D.; Gianni, Davide; Baker, David J.
Immunotherapies including PD-L1 blockade have shown remarkable increases in the T cell–directed antitumor response; however, efficacy is seen only in a minority of patients. Recently, pooled CRISPR-Cas9 knockout (CRISPRn) screens in tumor/immune co-culture systems have identified a number of genes that confer resistance to T cell killing in pathways including antigen presentation and cytokine signaling, providing insight into tumor mechanisms that cause resistance to immunotherapies. The development of an arrayed CRISPRn screen in a tumor/immune co-culture system would allow the identification of novel targets for immuno-oncology, characterization of hits from pooled screens, and multiple assay endpoints to be measured per gene. Here, a small-scale arrayed CRISPRn screen was successfully developed to investigate the effects on a co-culture of T cells and Cas9-expressing PC9 lung adenocarcinoma cells modified to express anti-CD3 antibody on the cell surface (PC9-OKT3 T cell system). A focused CRISPRn library was designed to target genes involved in known resistance mechanisms (including antigen presentation, cytokine signaling, and apoptosis) as well as genes involved in immune synapse interactions. The viability of PC9 cells was assessed in two-dimensional adherent co-cultures via longitudinal imaging analysis. Knockout of epidermal growth factor receptor (EGFR) and PLK1 in tumor cells cultured alone or with T cells resulted in increased tumor cell death, as expected, whereas knockout of the test gene ICAM1 showed subtle donor-specific resistance to T cell killing. Taken together, these data provide proof of concept for arrayed CRISPRn screens in tumor/immune co-culture systems and warrant further investigation of in vitro co-culture models.